2020
DOI: 10.1111/jth.14677
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of triggering receptor expressed on myeloid cells‐1 impairs thrombin generation

Abstract: Background:New evidence has shown the link between inflammation and thrombosis. Triggering receptor expressed on myeloid cells-1 (TREM-1) is an immunoreceptor expressed mostly on neutrophils and monocytes/macrophages. TREM-1 acts as an amplifier of the inflammatory response, and its pharmacological inhibition displays protective effects in various models of inflammatory disorders, in particular by dampening coagulation abnormalities and thrombocytopenia observed during acute inflammation.Objectives: We aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…TREM-1 is an immunoreceptor expressed mostly on neutrophils and monocytes/macrophages, and interestingly, recently, it is identified that acts on endothelial cells and regulates thrombin generation [ 37 , 38 ]. Current evidence showed that TREM-1 appears to augment inflammatory responses in infectious diseases [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 is an immunoreceptor expressed mostly on neutrophils and monocytes/macrophages, and interestingly, recently, it is identified that acts on endothelial cells and regulates thrombin generation [ 37 , 38 ]. Current evidence showed that TREM-1 appears to augment inflammatory responses in infectious diseases [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased presence of inflammation, neointimal formation, medial thickening, and plaque formation in RAPAs treated with scrambled peptide compared to LR12-treated arteries in this study supports the potency of ox-LDL in inducing plaque formation and inflammatory cell recruitment and the beneficial effects of LR12 peptide in attenuating inflammation and plaque formation [ 15 , 17 , 18 ]. This difference may have been associated with the effects of LR12, which has previously been shown to dampen the pro-thrombogenesis effects of TREM-1 [ 19 ]. LR12 inhibits the expression of tissue factors on monocytes and may reduce their activity in leukocyte-associated thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…TREM1 accelerates thrombin generation by inducing TF secretion and is an interesting target for investigating novel inhibitors of thrombotic activity. [ 46 ] In addition, TREM1 intervention partially compensates for FOXJ2‐ and SLAMF8‐induced TF secretion. These results provide novel evidence that FOXJ2 activation contributes to the pathogenesis of APS by repressing SLAMF8/TREM1‐mediated autophagy and inducing related inflammation and thrombosis.…”
Section: Discussionmentioning
confidence: 99%